2011
DOI: 10.7773/cm.v37i2.1840
|View full text |Cite
|
Sign up to set email alerts
|

Bryde’s whale (Balaenoptera edeni) in the southwestern Gulf of California: Relationship with ENSO variability and prey availability

Abstract: Interannual changes in the occurrence of Bryde’s whale (Balaenoptera edeni) have been observed in La Paz Bay (southwestern Gulf of California, Mexico) over the last 20 years. We suggest that these changes could be driven by natural fluctuations in food resources that are related to climate variability. We compared monthly Bryde’s whale occurrence in La Paz Bay from 1988 to 2006 to climate variability at seasonal and interannual time scales and its effect on prey availability. The results showed that Bryde’s wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The Hauraki Gulf is an important habitat for the species (Wiseman 2008, Wiseman et al 2011), but it is also a region of high shipping transit, which results in whale mortality caused by vessel-strike injuries (Stockin et al 2008, Wiseman 2008, Behrens 2009, Riekkola 2013, Constantine et al 2015. Our estimates are precise, robust to the assumptions of the models and could be used in the future to examine population trajectories over time and the impact of ship strikes on the longterm persistence of the population.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The Hauraki Gulf is an important habitat for the species (Wiseman 2008, Wiseman et al 2011), but it is also a region of high shipping transit, which results in whale mortality caused by vessel-strike injuries (Stockin et al 2008, Wiseman 2008, Behrens 2009, Riekkola 2013, Constantine et al 2015. Our estimates are precise, robust to the assumptions of the models and could be used in the future to examine population trajectories over time and the impact of ship strikes on the longterm persistence of the population.…”
Section: Discussionmentioning
confidence: 86%
“…In the Hauraki Gulf, it appears that there is a higher occurrence of whales during the austral winter (Wiseman et al 2011), although seasonality was not detected in a more recent study (Dwyer 2014). Bryde's whales in the Hauraki Gulf are subject to a high level of anthropogenic mortality, as evidenced by records of ship strikes and entanglements (Stockin et al 2008, Wiseman 2008, Riekkola 2013, Constantine et al 2015. From 1996 to 2014, a total of 44 whales were reported dead.…”
Section: Introductionmentioning
confidence: 99%
“…La Niña events have effects that are opposite to those of El Niño, although northern faunal intrusions into subtropical areas have seldom been reported [ 40 ]. In addition, ENSO impacts on prey availability have been documented for several marine mammal populations in the Northeast Pacific [ 41 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salvadeo et al [56] analysed the sighting records of Bryde's whales and environmental variability. They identified that changes in the occurrence of Bryde's whales were related to the interannual variability in the SST and Chl a in La Paz Bay.…”
Section: Discussionmentioning
confidence: 99%